Sprayed substance transfer and hard-melting composition formation in ion plasma system - Vasilenko, N.A.; Terpiy, D.N.; Vasetskaya, L.A. (Functional Materials, 2012)
Relation between characteristics of discharge and parameters of growing film when using ion-plazma methods of spraying has been shown at the example of magnetron spraying of TaB₂. Possibility of the modeling application for explanation of composition and properties of the films produced by such methods has been shown. Suggestions about the mechanism of formation and growth of hard-melting metal boride films have been made.